Analisis Karakteristik Pekerja Wanita Pada Usaha Batu Bata di Kecamatan Kuala Kabupaten Nagan Raya - Badli, S.E.,M.Si, Dr. Saiful; firman, firman; Helmi Noviar, Helmi; Syahril, Syahril; Azzahiri Fadlianur, Azzahiri (universitas teuku umar, 2025)
ABSTRACTThe pressed brick industry is one of the fastest growing sectors, particularly in Kuala Sub-district, Nagan Raya Regency, which has 539 brick industries. Women's participation in this industry not only supports the family economy but also contributes to the dynamics of the labor market and the welfare of their families. This study aims to describe the characteristics of the female workforce in the brick industry in Kuala District, using a descriptive qualitative method with random sampling technique involving 41 brick industries as samples. The results showed that the majority of female workers were in the age range of 39-40 years (43.1%) with an average work experience of three years (56.1%). The average wage received was Rp80 per unit of production, with daily productivity mostly ranging between 300-500 units. Keywords: characteristics, female labor, productivity